ANALISIS PENGARUH PERUBAHAN UU NO.36 TAHUN 2008, BEBAN PAJAK TANGGUHAN DAN PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur Terdaftar di BEI 2007-2008 dan 2011-2012) - Devi Intan Satyaningrum; Imam Ghozali (Diponegoro Journal of Accounting, 2016)
This study aims to test the effect of tax effect, deferred tax expense and tax planning as independent variables of earnings management measured using discretionary current accruals as dependent variable. This study has also used control variable, that are long term debt, company performance, and changes of company growth. The testing of the study was conducted mainly because there was change of Income Tax that companies take advantage for that to conduct earnings management.Type of data used in this study is secondary data. The population of the study is all manufacture companies listed in Indonesia Stock Exchange. To collect the sample, the writer employed purposive sampling method and applied criteria listed in Indonesia Stock Exchange, reported annually subsequently from 2007- 2008 and 2011-2012 in Indonesia Stock Exchange. There was deferred tax expense variable in financial report.The result of this study shows that deferred tax expense variable and tax planning significantly influenced the earnings management activities. Meanwhile, Tax effect variable or the impact of the change of Income Tax rate on UU No. 36 year 2008 did not influence earnings management activities or, in other words, there was not difference of earnings management in the companies before the change of tax policy which was from 2007-2008 and in the companies after the change of tax policy which was from 2011-2012.